2017
DOI: 10.1039/c7gc01012e
|View full text |Cite
|
Sign up to set email alerts
|

A PEGylated deep eutectic solvent for controllable solvothermal synthesis of porous NiCo2S4 for efficient oxygen evolution reaction

Abstract: A PEGylated deep eutectic solvent was developed and used for one step solvothermal synthesis of NiCo2S4 for efficient oxygen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 65 publications
5
95
0
Order By: Relevance
“…To optimize the OER performance of transition metal sulfides, several recent studies revealed that the introduction of secondary metal atoms into the crystal lattice effectively improves their catalytic activities ,. Binary‐transition‐metal compounds have been proven to be favorable for effectively enhancing catalytic performance for OER ,.…”
Section: Introductionsupporting
confidence: 88%
“…To optimize the OER performance of transition metal sulfides, several recent studies revealed that the introduction of secondary metal atoms into the crystal lattice effectively improves their catalytic activities ,. Binary‐transition‐metal compounds have been proven to be favorable for effectively enhancing catalytic performance for OER ,.…”
Section: Introductionsupporting
confidence: 88%
“…The ion-transportk inetics of the catalysts was analyzed by electrochemical impedance spectroscopy (EIS), and results are showni nF igure 4C.T he simplified equivalente lectrical circuit fitting the Nyquistp lots is shown in Figure S8, [26] in which the parameters R s , R c ,a nd C dl are the uncompensated series resistance, the charge-transfer resistance, and the accompanying double-layer capacitance, respectively.T he similar R s values of www.chemsuschem.org facilitatei mprovement of the charge-transport capability and furtherimprovethe OER performance. [26] Cyclic voltammetry( CV) was performedw ith differents can rates in the non-Faradaic region to measure C dl (FigureS9), [20] which is proportionalt ot he electrochemical active surface area (ECSA). As shown in Figure 4D, C dl decreases in the order of Co 0.47 Fe 0.53 P( 98 mF cm À2 ) > Co 0.63 Fe 0.37 P( 86 mF cm À2 ) > Co 0.24 Fe 0.76 P( 62 mF cm À2 ) > CoP (53 mF cm À2 ) > CoFeP-S (9 mF cm À2 ) > cobalt ferrite-2 (5 mF cm À2 ) > FeP (2 mF cm À2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ion-transportk inetics of the catalysts was analyzed by electrochemical impedance spectroscopy (EIS), and results are showni nF igure 4C.T he simplified equivalente lectrical circuit fitting the Nyquistp lots is shown in Figure S8, [26] in which the parameters R s , R c ,a nd C dl are the uncompensated series resistance, the charge-transfer resistance, and the accompanying double-layer capacitance, respectively.T he similar R s values of Co 0.47 Fe 0.53 P, Co 0.63 Fe 0.37 P, Co 0.24 Fe 0.76 P, CoP,c obalt ferrite-2 and FeP microspheres indicate ac onsistent experimental configuration. The R ct values follow the order of Co 0.47 Fe 0.53 P < Co 0.63 Fe 0.37 P < Co 0.24 Fe 0.76 P < CoP < cobaltf errite-2 < FeP (Figure 4C).…”
Section: Oer Catalytic Performanceofc O X Fe 1àx Pm Icrospheresmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a deep eutectic solvent consisting of thiourea and PEG-200 with a molar ratio of 1 : 2 was prepared on the basis of the reported method. 37 Then, Cu(NO 3 ) 2 $3H 2 O (1.0 g) was dissolved into the prepared deep eutectic solvent (40.0 g) under stirring. Aer that, the mixture was transferred into a stainless steel reactor with a Teon coating, and the reactor was maintained at 180 C for 24 h. Finally, the prepared CuS was washed with ethanol and water three times, and was dried under vacuum at 40 C for 24 h. The preparation process of PbS and ZnS was similar to that for preparing CuS.…”
Section: Preparation Of Metal Chalcogenides (Mc)mentioning
confidence: 99%